Active citizenship or activist citizenship? a framework for studying citizenship in new social movements and the role of ICTs - Papa, Venetia; Milioni, Dimitra L. (My University, 2013)
The latter half of the twentieth century witnessed an upsurge in mobilization and collective action by a wide range of activists and groups engaging in social and political protest, all over the world, which continues to this day. New media are not only greatly facilitating the ways in which activists communicate and protest, but are also altering the relation of the movements to territorial boundaries and localities. Scholars from a wide range of disciplines have tended to focus on questions about the internet’s role in protest, without attempting to answer the changing meaning of what it means to be a citizen within such movements and through their practices. This article responds to this need by developing an analytical framework for studying the connection between citizenship and ICT-mediated social movements, drawing on existing scholarship on social movements, citizenship and ICTs. Specifically, using citizenship studies as a starting point, it brings together elements that are necessary for a two-level analysis: a) the tangible aspects that are seen as the concrete practices of movements and their participants and b) the ideational aspects that are seen as the abstract practices of movements and their participants. This provides a theoretical structure that facilitates connections between different disciplines that might otherwise be difficult to discern, so that the construction of citizenship can be studied on an interdisciplinary basis.
Keywords: Civic engagement; Civic participation; Civic values; Protest; ICTs